Monitoring Dan Evaluasi Awal Tata Kelola Keuangan Sekolah Rakyat - Risnandar; Muhammad Ulinnuha (Universitas Merdeka Madiun, 2026)
This study aims to provide an initial monitoring and evaluation of financial governance in 20 community-based schools (Sekolah Rakyat) under the Ministry of Social Affairs of Indonesia. Using a mixed-method approach combining questionnaires, interviews, and field observations, the monitoring and evaluation (Monev) focused on three aspects: availability of financial management human resources, understanding of financial governance principles, and readiness of supporting infrastructure. Results show that while all schools have principals, one school lacks a treasurer and another lacks administrative staff. Educational background of financial managers is generally adequate, dominated by bachelor and master’s degrees. However, 51.72% of respondents demonstrate low understanding of financial governance, indicating urgent need for training and technical assistance. Infrastructure readiness is also limited, with 50% of schools categorized as inadequate. These findings highlight the importance of strengthening capacity building and resource allocation to ensure accountable and transparent financial governance in Sekolah Rakyat.